1991
DOI: 10.1128/mcb.11.4.1912-1920.1991
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Amino-Terminal Helix-Loop-Helix Domain of the vav Proto-Oncogene Activates Its Transforming Potential

Abstract: vav, a novel human oncogene, was originally generated in vitro by replacement of its normal 5' coding sequences with sequences from pSV2neo DNA, cotransfected as a selectable marker (S. Katzav, D. Martin-Zanca, and M. Barbacid, EMBO J. 8:2283-2290, 1989). The vav proto-oncogene is normally expressed in cells of hematopoietic origin. To determine whether the 5' rearrangement of vav or its ectopic expression in NIH 3T3 cells contributes to its transforming potential, we isolated murine and human proto-vav cDNA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Therefore, there was no RAP1B truncation in the 1G2-RAP1B clone. Of note, an N-terminal truncation is known to increase the oncogenic potency of VAV1 (56). Overall, we showed that HIV-1-induced aberrant host gene transcription at the integration site leads to aberrant host protein expression.…”
Section: Fig 4 Hiv-1 Proviruses Integrated Into Cancer-related Genes ...mentioning
confidence: 57%
“…Therefore, there was no RAP1B truncation in the 1G2-RAP1B clone. Of note, an N-terminal truncation is known to increase the oncogenic potency of VAV1 (56). Overall, we showed that HIV-1-induced aberrant host gene transcription at the integration site leads to aberrant host protein expression.…”
Section: Fig 4 Hiv-1 Proviruses Integrated Into Cancer-related Genes ...mentioning
confidence: 57%
“…Oncogenic Vav‐1 contains a deletion of the CH domain and is mildly transforming towards 3T3 cells but unable to potentiate NFAT‐dependent transcription (Katzav et al ., 1991; Wu et al ., 1995). Deletion of the N‐terminal 187 amino acids of Vav‐1 substantially enhances transforming potential; however, this mutant is still unable to potentiate NFAT‐dependent transcription in Jurkat T cells (Lopez‐Lago et al ., 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Another signaling molecule that is involved in Type I IFN signaling is the vav protoonco-gene (Vav). Vav is specifically expressed in cells of hematopoietic origin and contains src homology 2 (SH2) and src homology 3 (SH3) domains and guanine exchange factor motifs [99][100][101]. This protein undergoes tyrosine phosphorylation in response to a wide variety of stimuli in different cell types and participates in signaling induced by various cytokines (reviewed in [102][103][104]).…”
Section: Vav Proto-oncogene and Its Role In Interferon-dependent Grow...mentioning
confidence: 99%